Nukuhiva Berland, 1935 is a troglobitic wolf spider (Araneae: Lycosidae), not a nursery-web spider (Pisauridae) - Framenau, Volker W.; Lehtinen, Pekka T. (Zootaxa, 2015)
The monotypic genus Nukuhiva Berland, 1935 with N. adamsoni (Berland, 1933) as type species, is re-described and transferred from the Pisauridae Simon, 1890 (fishing or nursery-web spiders) to the Lycosidae Sundevall, 1833 (wolf spiders) based on genitalic and somatic characters. Nukuhiva adamsoni, originally described from French Polynesia, appears to inhabit mountainous habitats of volcanic origin. Its troglobitic morphology—comparatively small eyes and pale, uniform coloration—suggest it to be associated with subterranean habitats such as caves or lava tubes, similar to the Hawaiian troglobitic species Lycosa howarthi Gertsch, 1973 and Adelocosa anops Gertsch, 1973.